Electropolymerization of Aniline on Plastically Deformed Pd Surface: Structure at Micro- and Nano-Scale - Eftekhari, Ali; Kazemzad, Mahmood; Keyanpour-Rad, Mansoor (Polymer journal, 2006)
Electrochemical polymerization of aniline on the surface of a plastically deformed Pd electrode was investigated. Initially, the Pd electrode was subject of plastic deformation as a result of hydrogen insertion/extraction. Plastically deformed structure of the substrate has a significant influence on the electropolymerization process. In this case, an adherent film with smooth surface is formed. Although the plastically deformed surface is rougher than the conventional Pd surface, the polyaniline film electropolymerized is smoother in both micro- and nano-scale. This is of particular interest for applied purposes, as it guarantees higher stability of the conductive polymer. In addition, these results indicate the importance of surface structure of substrate electrode on electropolymerization process. On the other hand, it suggests Pd as a suitable substrate for the preparation of thin films of conductive polymers.